An OutKast Reader : Essays on Race, Gender, and the Postmodern South - Bradley, Regina N., 1984- (Book collections on Project MUSE., 2021)
"OutKast, the Atlanta-based hip-hop duo formed in 1992, is one of the most influential musical groups within American popular culture of the past twenty-five years. Through Grammy-winning albums, music videos, feature films, theatrical performances, and fashion, André "André 3000" Benjamin and Antwan "Big Boi" Patton have articulated a vision of postmodern, post-civil rights southern identity that combines the roots of funk, psychedelia, haute couture, R&B, faith and spirituality, and Afrofuturism into a style all its own. This postmodern southern aesthetic, largely promulgated and disseminated by OutKast and its collaborators, is now so prevalent in mainstream American culture (neither Beyoncé Knowles's "Formation" nor Joss Whedon's sci-fi /western mashup Firefly could exist without OutKast's collage aesthetic) that we rarely consider how challenging and experimental it actually is to create a new southern aesthetic. An OutKast Reader, then, takes the group's aesthetic as a lens through which readers can understand and explore contemporary issues of Blackness, gender, urbanism, southern aesthetics, and southern studies more generally. Divided into sections on regional influences, gender, and visuality, the essays collectively offer a vision of OutKast as a key shaper of conceptions of the twenty-first-century South, expanding that vision beyond long-held archetypes and cultural signifiers. The volume includes a who's who of hip-hop studies and African American studies scholarship, including Charlie Braxton, Susana M. Morris, Howard Ramsby II, Reynaldo Anderson, and Ruth Nicole Brown." --